Framework para governança sustentável: um estudo multicasos em universidades brasileiras - Bolzan, Cristina Izabel Moraes (2023)
This study aimed to analyze the association between the sustainable governance model and institutional performance in the context of Brazilian federal universities. The research has a qualitative approach, of an exploratory and descriptive nature, operationalized through multiple case studies, using as sources of evidence interviews carried out with eleven (11) Federal Universities in Brazil between the months of April to July 2022 and document analysis, using content analysis for data analysis purposes. The results reveal that there are associations between management practices related to the Environmental, Economic, Social, Governance and Education (EESGE) dimensions oriented to the Sustainable Development Goals (SDGs) and institutional performance that contribute to a sustainable governance model in federal universities Brazilians. As the main evidence regarding management practices for the sustainability of universities analyzed in the environmental dimensions, waste management, energy generation, recovery of degraded water and sustainable constructions, awareness and education campaigns environmental; economic, investment in energy and infrastructure, and sustainable public procurement; social, institutional plans and policies to serve a specific group, extension actions with an impact on society; governance, there are governance structures with the purpose of guaranteeing good practices, which demonstrates the way in which the institution's various actors act, associated with institutional plans and policies; and educational, Brazilian federal universities offer undergraduate and postgraduate courses with subjects focused on sustainability. Some universities have joined programs such as the Environmental Agenda in Public Administration (Agenda A3P) and the United Nations (UN) Global Compact. With regard to institutional practices, all federal universities state that they are aligned with the UN 2030 Agenda. Regarding strategies to promote sustainability, there are actions such as environmental responsibility, waste management, energy efficiency, and research. There are many sustainability challenges for institutions, such as budget issues, water resources management, air quality, carbon consumption, cutting-edge technology and cyber attacks. The analysis of the institutional performance of Brazilian federal universities indicates that the majority have a good performance in relation to sustainability practices, but it was observed that there is still no institutionalized environmental culture and that the lack of resources makes some sustainability practices unfeasible. A framework was developed integrating the themes of governance and sustainability, called sustainable governance for the purposes of this study, aiming to contribute to institutional performance. Therefore, the results suggest that considering EESGE management practices and institutional performance in federal universities in Brazil in an integrated way can provide a strategic look at sustainability, and contribute to the implementation of sustainable governance structures, create public value, achieve a superior institutional performance, as well as deepening studies on these topics.